OBJEK WISATA SEJARAH: SEJARAH DAN PERKEMBANGAN MERCUSUAR ANYER-BANTEN - lihah solihah; Jumardi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2021)
Anyer lighthouse is one of the evidences of the legacy of the Dutch East Indies government in Indonesia, more precisely in the province of Banten. In the construction process, this lighthouse has a long history. This lighthouse is believed to be the zero point of the Deandels Project, namely the construction of the Anyer-Panarukan road. The lighthouse building until now stands firmly that exudes arrogance on the beach, after being investigated, it turns out that the building that stands is not the first lighthouse building made. Thus, the author is interested in examining the history and development of the Anyer Lighthouse, Banten. The method used in this research is literature study and interviews for the results written empirically and theoretically